Konstrukcja narzędzia do pomiaru poczucia niesprawiedliwości w pracy według teorii J. S. Adamsa - Michałkiewicz, Anna; Dudek, Bohdan (Acta Universitatis Lodziensis. Folia Psychologica, 2010)
This paper outlines the process of developing an instrument for measuring the sense of inequity at work. The research tool we created enables the evaluation of work satisfaction, in the meaning of J.S. Adams's theory. In order to elaborate the method and make a preliminary selection of questions, we conducted a pilot study. As for the main research, it was to examine the theoretical accuracy and to prove the reliability of the questionnaire.